From Frictionless to Thoughtless: The Correlation between Seamless UI/UX and Impulsive Buying Behavior in Digital Payment Apps - Suandana, Ni Putu Widantari; Kherismawati, Ni Putu Eka (PT.KARYA GEMAH RIPAH, 2025)
The evolution of financial technology has shifted the focus of payment system design from security to